Análisis del discurso de la campaña electoral desarrollada por el candidato a presidente de la República Andrés Araúz en la cuenta de Twitter, noviembre 2020 - abril 2021. - Marchán Morales, Nelson Javier (2023)
The objective of the investigative work is to analyze the speech of the former candidate for president of the Republic Andrés Araúz during the electoral campaign, made on his Twitter account, during the period April - November 2021. Critical analysis was used to set the objectives. The inquiry is asynchronous, quantitative-qualitative and bibliographic; non-experimental design. The method used was analytical. Teun Van Dijk's matrix was used for the analysis because it is considered an effective tool to carry out discourse analysis. The matrix is divided into two planes that help to understand the messages transmitted in the speech. It was analyzed in a general way and the matrix was applied to each tweet comprising the study population. A total of 776 tweets were analyzed one by one. The results obtained through its analysis are reflected in the matrix established in this investigation. The candidate Andrés Araúz in his political speech on the social network Twitter proposes to give citizens hope and solidarity. He uses this space to spread attacks on his adversaries, he proposed to his voters to act legally and apply it firmly. In addition, he relied on international actors, such as former President Eco. Rafael Correa Delgado, to cement his image.